Trends in heat related illness: Nationwide observational cohort at the US department of veteran affairs - Thomas F. Osborne; Zachary P. Veigulis; Ambarish Vaidyanathan; David M. Arreola; Paul J. Schramm (Elsevier, 2023)
Introduction: Environmental heat can have a negative impact on health, leading to increased healthcare utilization, disability, and death. Specific clinical conditions, in combination with a global rise in temperature, may amplify the risk of heat related illnesses. Materials and Methods: We conducted a retrospective analysis of VA's national electronic health record database from January 1, 2002, through December 31, 2019. Heat related illness diagnoses were assessed for associations with patient demographics, comorbidities, and geographic residence at the time of a heat related illness diagnosis. Descriptive statistics, linear regression, and additive seasonal decomposition methods were utilized to assess risk factors and trends. Results: There were 33,114 documented cases of heat related illness, which impacted 28,039 unique patients, during our 18 year assessment period. Veterans were diagnosed with heat related illnesses in all 50 US states and there was an increase in the rate over time. The likelihood of heat related illnesses was greater for those with increased comorbidity burden. Rates increased for homeless Veterans in the first half of the assessment period, and then declined for the second half. Black, as well as American Indian/Alaska Native Veterans accounted for a greater proportion of heat related illnesses. Conclusion: There has been a statistically significant and clinically important increase in the incidence of heat related illnesses over time. There has also been an increased number of heat related diagnoses associated with existing health and demographic factors, and the increase over time did not strictly follow the expected geographic North-South climate trends.